Interwall Friction and Sliding Behavior of Centimeters Long Double-Walled Carbon Nanotubes - Zhang, Rufan; Ning, Zhiyuan; Xu, Ziwei; Zhang, Yingying; Xie, Huanhuan; Ding, Feng; Chen, Qing; Zhang, Qiang; Qian, Weizhong; Cui, Yi; Wei, Fei (Nano letters, 2016)
Here, we studied the interwall friction and sliding behaviors of double-walled carbon nanotubes (DWCNTs). The interwall friction shows a linear dependence on the pullout velocity of the inner wall. The axial curvature in DWCNTs causes the significant increase of the interwall friction. The axial curvature also affects the sliding behavior of the inner wall. Compared with the axial curvature, the opening ends of DWCNTs play tiny roles in their interwall friction.